Penerapan Pola Komunikasi Pada Perusahaan Perkebunan Karet PT Huma Indah Mekar Tulang Bawang Barat Provinsi Lampung - Irawan, Sahrul Ari; Alfarisy, M Ali Fikri (Sekolah Tinggi Ilmu Komunikasi Inter Studi, 2023)
Communication is very important in the implementation of various existing things, especially in carrying out various activities in the company. Communication patterns cannot be separated from the management activities of a company. Communication patterns describe two or more people who send and receive messages in a precise way so that the intended message can be conveyed or understood easily. This study aims to determine the application of communication patterns and find out the supporting factors for the application of communication patterns, as well as find out the obstacles that exist when implementing communication patterns at PT Huma Indah Mekar (HIM) Tulang Bawang Barat. The methods used in this study are qualitative method research, how to make observations, interviews, and literature or literature studies. The informants in this study were HRD, the head of the garden, the foreman of the garden care, and employees who were in the office (HRD staff). The results of this study show that PT Huma Indah Mekar has a communication pattern of wheel, Y, circle, chain, and all directions. Supporting factors are communication patterns, language acquisition, means of communication, thinking skills, and a good environment. Obstacles in implementing communication patterns are natural factors and HR itself.